1990
DOI: 10.1021/ma00226a007
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes of linear polymers in the glassy state

Abstract: Internal stresses in glassy polymer materials arise from two different sources; deviation of polymer conformation from its equilibrium state and change of intersegment distances. These stress components may be separately observed by carrying out simultaneous measurements of tensile stress and birefringence relaxations of polymer films, assuming that they are additive. It is pointed out that the change of intersegment distances occurs first, and conformational deformation is gradually induced if a glassy polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…In a phenyl polymer such as PS, optical birefringence has two distinct sources: (1) birefringence arising from bond stretching distortions through changes in interatomic distances, primarily in the carbon-carbon backbone, and (2) birefringence arising from molecular alignment through nonrandom molecular conformations and in the case of PS especially the phenyl side group. 30 In terms of the constitutive model employed in this work (see below) bond stretching is associated with a deviatoric stress state S b and nonrandom molecular conformations are associated with a deviatoric stress state S c . For sufficiently small degrees of optical anisotropy, and assuming optic axes coincide with principal axes of stress, each contribution will obey a linear stress-optical rule relating the birefringence Δn to the corresponding differences in principal stress through a stress-optical coefficient C:…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a phenyl polymer such as PS, optical birefringence has two distinct sources: (1) birefringence arising from bond stretching distortions through changes in interatomic distances, primarily in the carbon-carbon backbone, and (2) birefringence arising from molecular alignment through nonrandom molecular conformations and in the case of PS especially the phenyl side group. 30 In terms of the constitutive model employed in this work (see below) bond stretching is associated with a deviatoric stress state S b and nonrandom molecular conformations are associated with a deviatoric stress state S c . For sufficiently small degrees of optical anisotropy, and assuming optic axes coincide with principal axes of stress, each contribution will obey a linear stress-optical rule relating the birefringence Δn to the corresponding differences in principal stress through a stress-optical coefficient C:…”
Section: Sample Preparationmentioning
confidence: 99%
“…In fact, several authors have exploited this to show that the total birefringence changes sign during small strain stress-relaxation experiments, since the bond stretching stress relaxes faster than the conformational stress. 30,34 On this basis we can extend the mechanical constitutive model to include birefringence in a glassy polymer such as PS. For example, when an isotropic PS is loaded to an infinitesimal strain state ε in the glassy state, parallel coupling means the bond stretching and conformational arms of the model are subject to identical strains.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Biomineralization is a phenomenon that is observed in a wide variety of organisms, and in most cases, acidic organic matter such as acid proteins is involved in it [4]. In coccolithophorids, acid proteins have not been found in coccoliths, but acid polysaccharides are considered to participate in coccolith formation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, McKenna [39] reported that the rate of polymer relaxation in the glassy state (i.e., concerted movement of polymer segments to increase polymer self-association that leads inexorably toward a thermodynamically metastable end state) is autoretarded, and that the time-dependent change of a given property, such as volume or density, can be expressed by a linear combination of stretch-exponential functions [39-411. These are similar in form to the linear combination of exponential decay functions that express desorption of molecules entrapped in the glassy state of polymers samples prepared via evaporation-induced transition to a glassy state at constant temperature, as described above. It is also well known [42][43][44][45] that internal stresses in a glassy polymer accumulate with polymer "relaxation", owing to a corresponding accumulation of tension along the backbone of the segments between relatively non-yielding well-associated microdomains of polymer, which makes the next polymer relaxation event more difficult to occur. This in part contributes to the auto-retardation in the rate of polymer relaxation observed by McKenna.…”
Section: Synergistic Interactions In the Kinetics Of Desorption And Omentioning
confidence: 99%